Toward a framework for assessing the 'global' and 'citizen' in global citizenship education in Australia and beyond. Issue 5 (3rd September 2021) - Thomas, Matthew A. M.; Banki, Susan
ABSTRACT: In addition to its influences across economic, geopolitical, and social spheres, globalization has given rise to the notion of a 'global citizen' who is able to understand a shifting and more internationalized world while moving fluidly through it. Education has been trumpeted as the means to achieve this globally-aware citizenry, leading to an entire field of global citizenship education (GCE). Here teachers are the linchpin, yet understandings of globally-focused coursework in teacher education remain underdeveloped. This paper explores the 'global' within core courses in initial teacher education in Australia and interrogates the kinds of 'citizens' to be cultivated. We begin in our pilot study by canvassing university courses across Australian Group of Eight universities, and locating more global aspects of the courses, where available. Based on initial findings, we offer a dual-axis conceptual framework for guiding an 'alternative future' for GCE within teacher education. We then use the framework in a focused coding of one teacher education syllabus as an exemplar of its potential utility for examining the ways in which future teachers are encouraged, or not, to engage with broader geopolitical, sociocultural, and economic forces of globalization in the PreK-12 schools in which they will eventually teach.